The Effect of Agency Services on Service User Satisfaction in PT. Serasi Shipping Indonesia - Leonard Togatorop, Agus; Markus Yando; Irsyad Assyiroth (Dinasti International Journal of Digital Business Management, 2022)
Indonesia is a country known as a maritime country, most of which is waters and consists of islands. Therefore, sea transportation is very important to connect the islands scattered throughout Indonesia. Shipping is one of the means to serve the movement of goods and services from one island to another. Based on this, facilities and infrastructure are needed that can support the smooth operation of export and import service tools. Thus, agency services are needed to be able to support these shipping activities. PT. Serasi Shipping Indonesia Jakarta is a company engaged in the agency of foreign ships and local ships